Dosimetric comparison of fixed field dynamic IMRT and VMAT techniques in simultaneous integrated boost radiotherapy of prostate cancer. Issue 50 (16th December 2022) - Sun, Haitao; Wang, Ning; Huang, Guosen; Liu, Xiangping
Abstract : High-risk prostate cancer can take advantage of the combination of hypofractionated radiotherapy and pelvic conventional fraction radiotherapy. The comparison between fixed field dynamic IMRT and VMAT techniques can provide suggestions for clinical treatment. We selected 10 high-risk prostate cancer patients who received radiotherapy at the cancer center of Sun Yat-sen University from January 2016 to December 2019. The targets contained in prostate, seminal vesicles and pelvic lymph nodes. With the same prescription and optimized parameters, 9F, single-arc (1ARC) and double-arc (2ARC) treatment plans were developed. The dose distribution of the targets, OAR, MU, treatment time and gamma pass ratios of dose verification was compared. The D2% (69.37 ± 0.89) Gy, D50% (66.92 ± 0.63) Gy, HI (0.09 ± 0.02), and CI (0.83 ± 0.05) of PTV1 in 9F were slightly better than those of 1ARC which were (71.13 ± 1.21) Gy, (68.50 ± 0.76) Gy, (0.12 ± 0.02), (0.74 ± 0.07), except D98%, the difference was significant ( P  < .05). All dosimetry indices of PTV1 in 9F and 2ARC were close and have no significant differences ( P  > .05). The V95% (99.45 ± 0.78)% of PTV2 in 9F was slightly better than that in 1ARC (99.35 ± 1.28)%. The difference was significant ( P  < .05). All dosimetry indices of PTV2 in 9F and 2ARC were close and the difference was not significant ( P  > .05). The Dmean of the bladder and the V67.5 Gy of rectum between all three plans were similar. The Dmean of left and right femoral in 1ARC and 2ARC were lower than that in 9F, and the difference was significant ( P  < .05). Other dosimetry indices of OARs in 9F were lower than those in 1ARC and 2ARC, and much lower than 1ARC. The difference was significant ( P  < .05). Mean monitor units in 1ARC and 2ARC were fewer by 70.0% and 67.2% in comparison with 9F. The treatment mean time in 1ARC and 2ARC was shorter by 81.7% and 61% in comparison with 9F. Verification pass ratios of γ (3%/3 mm) were 97.8% (9F), 98.9% (1ARC) and 99.4% (2ARC) respectively. The difference was significant ( P  < .05). Compared with IMRT, VMAT improved delivery efficiency noticeably. Two arcs provided comparable tumor dosimetry coverage, but performed worse in dose sparing for bladder, rectum and small bowel. The IMRT plan was preferable to VMAT in prostate cancer simultaneous integrated boost radiotherapy.